STANDARD OPERATING PROCEDURE OF JAHAR MOHRA PISHTI: A POTENT CARDIO TONIC - Kaushik, *Peeyush; Rani Ahuja, Meena; Dhyani, Akanksha; Bhatt, Dinesh; Goel, Anjali (International Journal of Ayurveda and Pharma Research, 2016)
In the era of science and sagacity every sighting needs proofs and confirmations of its authenticity and when it comes to a medicinal preparation, the qualms are a step higher. Thus establishing pharmacopeial standards for a potent cardiotonic like Jahar Mohra Pishti is the need of time. Till date no work has been performed on standard operating procedure or standardization of Jahar Mohra. So, various available data was collected for complete documentation in terms of chemical composition, crystal structure, physicochemical analysis, therapeutic activity and method of proper storage so as to draw a standard operating procedure for the formulation.Jahar Mohra is named as Naga Pashana in most of the classical text of Ayurveda. Chemical formula for Jahar Mohra was evaluated through results of XRD and was Hydrous Magnesium Silicate i.e. Mg3-xSi2O5(OH)4-2x which is a basic formula for Serpentine group of minerals. Three samples of Jahar Mohra Pishti were prepared as per Siddha Yoga Sangraha to set the Standard Operating Procedure. Raw material was purified with lukewarm demineralised water. The Pisthi was prepared by impregnating and triturating the powdered samples with Gulab Arka (Rose Water) for 14 times. Observations were recorded during each step and a conclusion was drawn.